Analisis Hubungan Peranan Budaya Perusahaan terhadap Penerapan Good Corporate Governance pada PT Aneka Tambang Tbk - Rindang Widuri; Asteria Paramita (Bina Nusantara University, 2007)
This article examines the relationship between company cultures with Good Corporate Governance (GCG). It used survey method and correlational technique by distributing questioner with two instruments, namely company cultures and GCG. The respondents were employees of PT. Aneka Tambang Tbk consisting of 100 persons for which 87 persons were selected determined using Sugiyono books formula. The sample were determined using simple random sampling. The study used simple linear regression and simple cr relational technique. The results show that there is a strong correlation between company culture and GCG. It means that the stronger of company culture implementation the more intention to implement GCG.